IDEAL FUZZY NEAR-RING - Saman Abdurrahman; Na'imah Hijriati; Thresye Thresye (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2012)
In this paper will be discussed ideal near-ring, ideal fuzzy near-ring covering the relationship between ideal near-ring and ideal fuzzy near-ring.